Plantations, privatization, poverty and power : changing ownership and management of state forests - Garforth, Michael; Mayers, James (Earthscan, 2005)
"Examines the evidence and explores the many issues raised by changing relationships between the state, the private sector and local livelihoods. Key lessons in how governments can best achieve a balance between private and public involvement are provided by seven case studies from Australia, China, Chile, India, New Zealand, South Africa and the United Kingdom"--Provided by publisher
Keywords: Forest reserves -- Management.; Tree farms -- Management.; Private forests -- Management.; Réserves forestières -- Gestion.; Forêts privées -- Gestion.; NATURE -- Natural Resources.; BUSINESS & ECONOMICS -- Environmental Economics.; BUSINESS & ECONOMICS -- Green Business.; Forest reserves -- Management; Tree farms -- Management; Forstwirtschaft; Plantagenwirtschaft; Privatisierung; Staatsforst; Vermögenspolitik; Waldbesitzer; Electronic books.; Aufsatzsammlung.